Research on coupling evacuation of escalator and staircase in fire scenario - Chunhua Zhang; Xin Wu; Hai Shen (PLoS ONE, 2025)
In order to improve mall evacuation efficiency, Pyrosim software and Anylogic software are used to study the coupled evacuation of mall personnel using escalators and stairs in a fire scenario. The available safe evacuation time of each evacuation exit was explored by analyzing the smoke transport, temperature, CO concentration and visibility of each floor of the mall under different fire source locations when the fire shutter was lowered to 1.8m from the ground. Then, the evacuation model of mall personnel under fire scenario was built by using Anylogic to compare and analyze the evacuation time of mall personnel using escalators coupled with stairs and stairs only, and analyze the evacuation time of personnel using escalators coupled with stairs when the fire shutter at the escalator is down to 1.8m from the ground and when the fire shutter is not down. The study shows that when the fire source is located on the top floor of the mall, the smoke does not affect the evacuation of people on other floors during the simulation time. Under the fire scenario, the escalator-coupled staircase evacuation can shorten the maximum evacuation time by 23.37% compared with the staircase only. The fire shutter descends to 1.8m from the ground and the evacuation efficiency is 6.41% higher than when the fire shutter is not descended. This research contributes to the enhancement of mall safety and has practical implications for future emergency management strategies in public spaces.